Pengaruh Kualitas Sistem Informasi Terhadap Kepuasan Pengguna Pada SMA Al – Huda Cengkareng - Imam Mahfuji Jaya; Jenie Sundari (LPPM Universitas Dian Nuswantoro, 2017)
Application of Information Systems becomes an absolute necessity and can provide a competitive advantage, thus becoming the highest priorities. Assessment Information System is a system studied its impact on user satisfaction in the neighborhood of Al-Huda School. In this study tested the effect of the quality of information systems against user satisfaction using the basic method of success DeLone and McLean. This study uses a quantitative approach to mapping the characteristics of the data by means of descriptive statistics. The results showed that the Quality System (X1) and quality information (X2) effect either jointly against user satisfaction (Y) Information System Assessment. T significant value to the quality of the system is smaller than the specified α (α = 0.05) is 0.000. In addition, the results of this test also showed the value of t is greater than t table (2.871> 1.686) for the quality of the information system, Based on the test results it can be concluded that H0 is accepted and Significance for 0,000 t of quality information. So the probability value 0.00 <0.005 and t value greater than t table (2.973> 1.686), so it can be decided that H1 is accepted. This means that the quality of information has positive influence on user satisfaction, the results of the study also concluded that the quality of the information system has a dominant influence on user satisfaction.